EXPERIMENTAL EVALUATION OF THE IMPACT OF MATERNAL CONSUMPTION OF AQUEOUS LEAF EXTRACT OF HYBANTHUS ENNEASPERMUS ON PREGNANCY IN SPRAGUE DAWLEY RATS - Awobajo, Funmileyi Olubajo; Adegoke, Adefunke Olufeyisipe; Iranloye, Olubusola Bolanle; Olatunji-Bello, Ibilola Ibiyemi (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The impact of aqueous leaf extract of Hybanthus enneaspermus (HEaq) on pregnancy factors and litter survival was investigated in Sprague Dawley (SD) rat. Control group received distilled water while the test group received 2g/kg body weight of HEaq orally. Blood samples were collected on days one and twenty of pregnancy for total blood count, serum thyroid hormone, thyroid stimulating hormone (TSH) and thyrotropin releasing hormone (TRH) assay. Half the number of rats in each group was sacrificed on day nineteen of pregnancy and the placenta and foetus were removed and weighed. The second half carried their pregnancy to term. Number and weights of litter were recorded at birth and the litter were also subjected to righting reflex test. Post-natal survival rate was determined for each group while effect of HEaq was also examined in-vivo on the activities of pregnant myometrial muscle. HEaq significantly decreased (p<0.05) foetal weight, placenta weight, foetal growth and survival, number and weights of litter at birth, maternal serum triiodotyroxine T3 and TSH level. Mean corpuscular haemoglobin, white blood cell count, platelet count and lipid profile were significantly increased (P<0.05). HEaq increased the frequency and percentage contraction of gravid myometrial muscle in a dose dependent manner. Maternal consumption of aqueous leaf extract of Hybanthus enneaspermus adversely affected pregnancy and development of the foetus, as it precipitated resorption of developing foetus and reduced size and weight of litter at term.